Digital Divide in Smart Sports Applications for the Elderly and Its Mitigation - Liu, Yongsen; Shan, Yu; Zhang, Mufan; Ji, Bin; Zhou, Yang (Quality in Sport, 2025)
Physical exercise for the elderly is not only an inevitable choice for addressing individual health crises but also a strategic necessity for alleviating pressure on medical resources and building an active aging society. Through methods such as literature review and logical analysis, this study focuses on the digital divide faced by the elderly in smart sports applications. By examining the application of smart sports in elderly physical exercise and the manifestations of the digital divide, it proposes mitigation pathways to provide theoretical references and practical insights for constructing an age-friendly digital health ecosystem, thereby enhancing the physical health of the elderly. The research indicates that smart sports applications for the elderly involve five key aspects: health monitoring and risk, personalized exercise prescription systems, virtual reality and immersive training, social motivation, and remote rehabilitation integrated with smart elderly care. The digital divide primarily manifests in three dimensions: technological access barriers, disparities in digital literacy and cognitive abilities, and psychological and social exclusion. At its core, the digital divide reflects a conflict between the logic of technological iteration and the demand for social equity. Based on this, the study constructs a three-dimensional mitigation framework of "technological optimization-social support-policy," proposing solutions through age-friendly technological redesign, multi-stakeholder collaboration mechanisms, and inclusive policy design.